A novel nanohybrid for cancer theranostics: folate sensitized Fe2O3 nanoparticles for colorectal cancer diagnosis and photodynamic therapy. Issue 21 (11th May 2017) - Nandi, Ramesh; Mishra, Snehasis; Maji, Tuhin Kumar; Manna, Krishnendu; Kar, Prasenjit; Banerjee, Saswati; Dutta, Shreyasi; Sharma, S. K.; Lemmens, Peter; Saha, Krishna Das; Pal, Samir Kumar
Abstract : Folic acid functionalized iron oxide nanoparticles for colorectal cancer theranostics application. Abstract : Organic–inorganic nanohybrids are becoming popular for their potential biological applications, including diagnosis and treatment of cancerous cells. The motive of this study is to synthesise a nanohybrid for the diagnosis and therapy of colorectal cancer. Here we have developed a facile and cost-effective synthesis of folic acid (FA) templated Fe2 O3 nanoparticles with excellent colloidal stability in water using a hydrothermal method for the theranostics applications. The attachment of FA to Fe2 O3 was confirmed using various spectroscopic techniques including FTIR and picosecond resolved fluorescence studies. The nanohybrid (FA–Fe2 O3 ) is a combination of two nontoxic ingredients FA and Fe2 O3, showing remarkable photodynamic therapeutic (PDT) activity in human colorectal carcinoma cell lines (HCT 116) via generation of intracellular ROS. The light induced enhanced ROS activity of the nanohybrid causes significant nuclear DNA damage, as confirmed from the comet assay. Assessment of p53, Bax, Bcl2, cytochrome c (cyt c ) protein expression and caspase 9/3 activity provides vivid evidence for cell death via an apoptotic pathway. In vitro magnetic resonance imaging (MRI) experiments in folate receptor (FR) overexpressed cancer cells (HCT 116) and FR deficient human embryonic kidney cells (HEK 293) reveal the target specificity of the nanohybrid towards cancer cells, and are thus pronounced MRI contrasting agents for the diagnosis of colorectal cancer.